2019
DOI: 10.1002/ajmg.a.61361
|View full text |Cite
|
Sign up to set email alerts
|

Emotional functioning among children with neurofibromatosis type 1 or Noonan syndrome

Abstract: While neurofibromatosis type 1 (NF1) and Noonan syndrome (NS) are clinically distinct genetic syndromes, they have overlapping features because they are caused by pathogenic variants in genes encoding molecules within the Ras-mitogen-activated protein kinase signaling pathway. Increased risk for emotional and behavioral challenges has been reported in both children and adults with these syndromes. The current study examined parent-report and self-report measures of emotional functioning among children with NF1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 64 publications
(92 reference statements)
3
15
0
Order By: Relevance
“…Another important finding is that 28% of our sample have anxious symptomatology, consistent with previous findings describing a high prevalence of anxiety traits and ADHD in children with NS when compared to the general population [19]. Several authors have reported that anxious symptoms are important predictors of future development of depressive disorders, and an increased risk of worse outcomes of depressive episodes in terms of greater depressive long term morbidity as well as an increased risk in suicidal behavior [44][45][46]59]. Indeed, several studies have reported a high prevalence of depressive disorders in adults diagnosed with NS [1,21,29], and a high prevalence of NS subjects have been reported to need an antidepressant treatment during adult ages [21].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Another important finding is that 28% of our sample have anxious symptomatology, consistent with previous findings describing a high prevalence of anxiety traits and ADHD in children with NS when compared to the general population [19]. Several authors have reported that anxious symptoms are important predictors of future development of depressive disorders, and an increased risk of worse outcomes of depressive episodes in terms of greater depressive long term morbidity as well as an increased risk in suicidal behavior [44][45][46]59]. Indeed, several studies have reported a high prevalence of depressive disorders in adults diagnosed with NS [1,21,29], and a high prevalence of NS subjects have been reported to need an antidepressant treatment during adult ages [21].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, nearly a half (46%) of our cohort with NS shows at least a DESR profile (dysregulation profile or deficient emotional self-regulation), highlighting emotional dysregulation problems as a relatively common feature. This latter finding confirms the general clinical evidence that subjects with ADHD (with and without genetic syndromes) often show emotional dysregulation [37,39,[43][44][45][46], and raise questions on the psychopathological characterization and the future development of this unspecific clinical feature. Some authors have reported that a very severe dysregulation profile rated with CBCL-AAA is highly related with the progression to a full syndromic pediatric bipolar disorder, frequently associated with ADHD [57].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…For example, impairments in general cognitive/ executive function, learning and social skills, anxiety and depression are associated with NF1 [4][5][6]. This is more than a social myth that comes from appearance, because these impairments are caused by pathogenic variants in genes encoding the Ras-mitogenactivated protein kinase signaling pathway [18]. These neurological and emotional features have significant negative impacts on QOL [19,20].…”
Section: Discussionmentioning
confidence: 99%